Comparação do cultivo celular 2D versus 3D em linhagem de adipócitos viscerais humanos tratados com irisina sobre os efeitos do pseudo SARS-COV-2 - Rocha, Paula Barreto da [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Introduction: Since the beginning of the COVID-19 pandemic, there has been a collective effort aimed at understanding the behavior of the SARS-CoV-2 virus and, thus, developing effective treatments; however, the literature on the relationship between the virus and adipose tissue is scarce. Obesity is among the biggest negative prognostic factors given its chronic pro-inflammatory characteristic. Irisin, an endogenous myokine produced during physical exercise, can influence viral infection in obese individuals. Although monolayer (2D) cell culture studies are the standard for preclinical studies, three-dimensional (3D) culture is more similar to the in vivo environment, enabling the development of new drugs that more faithfully mimic the repercussions of the various possible interactions. Comparison of techniques can enable the development of reproducible studies. Objective: To compare 2D and 3D cell cultures of human visceral adipocyte lineage treated with irisin and infected by Pseudo SARS-CoV-2. Materials and Methods: Monolayer (2D) and three-dimensional (3D) cell cultures of human visceral pre-adipocytes were used to carry out the study, consisting of 4 groups: Control Group (C): adipocytes without treatment; ACE2 Group: adipocytes treated with Angiotensin- Converting Enzyme-2 (ACE2), ACE2+PV Group: adipocytes treated with SARS-CoV-2 pseudovirus (PV) and ACE2+I+PV Group: adipocytes treated with 20nM irisin for 24h and with Pseudo SARS-CoV-2. In these cell cultures, the uptake of fluorescence levels for Pseudo SARS-CoV-2 and ACE2 was measured. Results: Irisin treatment promoted a decrease in pseudo SARS-CoV-2 uptake levels for 2D (G3, 48796±321 vs G4, 44801±328) and 3D (G3, 51540±214 vs G4, 47027±165) in both cell culture models. For all differences, p<0.001 was observed. Conclusion: 3D culture of human visceral adipocytes showed similar results to those of monolayer culture, suggesting that both techniques can be used in future studies.

Introdução: Desde o início da pandemia da COVID-19, há um esforço coletivo visando entender o comportamento do vírus SARS-CoV-2 e, assim, desenvolver tratamentos eficazes; entretanto, a literatura acerca da relação do vírus com o tecido adiposo é escassa. A obesidade está entre os maiores fatores de prognóstico negativo dada sua característica pró-inflamatória crônica. A irisina, miocina endógena produzida durante o exercício físico, pode influenciar na infecção viral em indivíduos obesos. Embora estudos de cultura celular monocamada (2D) sejam o padrão para estudos pré-clínicos, a cultura tridimensional (3D) se assemelha mais ao ambiente in vivo, viabilizando o desenvolvimento de novos fármacos mimetizando de forma mais fiel as repercussões das diversas interações possíveis. A comparação das técnicas pode viabilizar o desenvolvimento de estudos com reprodutibilidade. Objetivo: Comparar os cultivos celulares 2D e 3D da linhagem de adipócitos viscerais humanos tratados com irisina e infectados por Pseudo SARS-CoV-2. Materiais e Métodos: Cultura celular em monocamada (2D) e tridimensional (3D) de pré-adipócitos viscerais humanos foram utilizadas para realização do estudo, composto por 4 grupos: Grupo Controle (C): adipócitos sem tratamento; Grupo ACE2: adipócitos tratados com Enzima Conversora de Angiotensina-2 (ACE2), Grupo ACE2+PV: adipócitos tratados com pseudovirus SARS-CoV-2 (PV) e Grupo ACE2+I+PV: adipócitos tratados com irisina 20nM por 24h e com Pseudo SARS-CoV-2. Nessas culturas celulares foram mensuradas a captação dos níveis de fluorescência para Pseudo SARS-CoV-2 e ACE2. Resultados: O tratamento com irisina promoveu diminuição nos níveis de captação do pseudo SARS-CoV-2 para culturas de adipócitos viscerais humanos 2D (G3, 48796±321 vs G4, 44801±328) e 3D (G3, 51540±214 vs G4, 47027±165) em ambos os modelos de cultura celular. Para todas as diferenças foi observado p<0,001. Conclusão: A cultura 3D de adipócitos viscerais humanos apresentou resultados similares àqueles da cultura monocamada, sugerindo que ambas as técnicas podem ser usadas em estudos futuros.
Comparison of 2D versus 3D cell cultures in human visceral adipocyte lines treated with irisin on the effects of Pseudo Sars-CoV-2
Keywords: COVID-19; Técnicas de cultura de células em três dimensões; Microscopia confocal; Obesidade; 3D Culture; Obesity; Covid-19; Irisin; Confocal microscopy